Metathesis in metal – organic gels (MOGs) : a facile strategy to construct robust fluorescent Ln‐MOG sensors for antibiotics and explosives - Qin, Zheng-Sheng (2020)
It is essential to develop new effective sensor materials for the detection of antibiotics and organic explosives, due to their negative impacts on ecosystems and human health. In this work, guided by an in situ metal‐node metathesis approach, a fluorescent metal–organic gel [MOG(Eu) gel] has been synthesized for the first time by metal‐ion exchange between Eu3+ and Al3+ in the nonfluorescent MOG(Al) gel. More importantly, the postsynthetic MOG(Eu) xerogel shows remarkable selective detection ability towards ronidazole (RDZ), ornidazole (ODZ), metronidazole (MDZ), and dimetridazole (DTZ) antibiotics, as well as 4‐nitrophenol (4‐NP), with low detection limits of 1.205, 0.542, 0.999, 0.377, and 1.582 ppm, respectively. The high quenching efficiencies can be attributed to the decrease of effective energy transfer in the host–guest systems. The strategy of metathesis opens up new opportunities for synthetic methods and functional applications in MOGs materials.